O corpo na transversal do tempo: da sociedade disciplinar à sociedade de controle ou da analítica de "um corpo que cai - Silva, Edivaldo Vieira da (2006)
In the flux of events that have revolved certainties and truth regimes in the last decades, the thesis The Body in the Transversal of Time: from disciplinary society to society of control or the analytics of a body that falls projects itself in the plane of consistency of the contemporary society to analyze the recent technological innovations, which converge to the development of a new scientific paradigm. This paradigm is based on the strategy of making a force field as Converging Technologies or synergistic convergence NBIC (Nanotechnology, Biogenetics, Information Technology and Cognitive Science) of knowledges that are unified for a common target, i.e., the elementary structures of matter (the atom, the genes, molecules and cells). Technologies are analytically conceived based on Gilles Deleuze and Michel Foucault s arguments that consider machinic arrangements subject to the capitalist mega-machine or technologies of power and bodies seizure or what remains from them and subjectivities. In the plane of consistency of contemporary society, which presents it self as society of control, this investigation attempts to cartograph, at the same time, places of counter-positions and resistances